Literature Review Related To The Accounting Information System And Performance In Jordanian Companies - Zeyad Almartaneh; Nimer Alsihat; Nehad Ibrahim Ineizeh; Obada Jebreen Hussein; Baker Akram Falah Jarah (WSEAS Press, 2024)
Indexed by Scopus